KAJIAN TAKARAN PUPUK HAYATI PELARUT PHOSPAT DAN KOMPOS TERHADAP HASIL TUMPANGSARI JAGUNG (Zea mays. L) DENGAN WIJEN (Sasamum indicum. L) DI KECAMATAN PLAYEN KABUPATEN GUNUNG KIDUL - Heriyanto (JURNAL TRITON, 2016)
The Study On Compost And Phosphate Solvent Biological Fertilizer Dose On Corn And Sesame Multiple Cropping In Playen Sub District Gunung Kidul was performed in order to know the influence of phosphate solvent biological fertilizer, compost and the combination to the results of corn and sesame multiple cropping on dry vertisol soil in Bandung village, Playen sub district, Gunung Kidul held April 1 to October 31, 2015. The research design used a factorial arranged in a randomized complete block, comprising two factors the dose of compost with the levels of 5 tons/ha, 10 tons/ha, 15 tons/ha, 20 tons/ha and phosphate solvent biological fertilizer levels 0.0 g/plant, 0.5 g/plant, 1.0 g/plant, 1.5 g/plant repeated 3 times for each treatment. Aplication of compost was done in conjunction with tillage while phosphate solvent biological fertilizer was applied at the time of planting. The study reseults showed that introducing 20 tons/ha compost can increase the production of sesame 129.25 percent compared to the treatment of 5 tons/ha compost and the provision of phosphate solvent biological solvent fertilizer of 1.5 g biomass/plant increased the production of sesame by 68.43 percent. The giving a combination of 20 tons/ha compost and phosphate solvent biological fertilizers of 1.5 g biomass the crop production of sesame increased by 195.56 percent but production of maize dropped.